THE USE OF LINE WEBTOON COMIC STRIPS TO UPGRADE STUDENTS’ VOCABULARY MASTERY - Maharani, Luh Putri (Yavana Bhasha : Journal of English Language Education, 2021)
Vocabulary is the key for the learners’ language change in learning as a foreign language including English. However, Indonesian students still have problems in vocabulary building, particularly to memorize meaning of new words. This fact implies that they need effective ways to learn vocabulary. It would be more beneficial to use an effective vocabulary teaching technique to help the students in upgrading their vocabulary mastery. The use of relevant media in teaching vocabulary will also boost student’s motivation. The aim of this study was to reveal how Line Webtoon comic can be used to teach vocabulary, the student’s vocabulary mastery, and the student’s responses toward the use of Webtoon comic. The participants in this study were ninth-grade students and their English teacher. This research applied qualitative design. The data was gathered through observation during online learning in Google Classroom, student’s task and the interview process. Based on the data, the process of using Line Webtoon for ninth graders was successfully upgraded the students’ vocabulary mastery and motivation to read through online comic. It also showed that the students were interested to read because Webtoon consisted of many pictures and they were able to get many new words by using online media.